An empirical study on the performance and cointegration analysis of CPF approved unit trusts in Singapore. - Cheung, Alicia Wai Lai. (2009)
The objective of this study is to evaluate the performance of CPF Approved Unit Trusts in Singapore from May 1990 to June 1995. The Singapore unit trust industry has been in operation for more than three decades. Recently, an increasing number of articles on the local unit trust industry has been published. This new public interest is largely due to the Government's liberalisation in allowing the use of CPF fund for investment purposes. This study focuses on only CPF Approved Unit Trusts as it is envisaged that the recent moves by the Government will generate even more interest in CPF approved unit trusts. The methodology used to evaluate the performance included analysis of publicly available information compiled on a monthly basis over the period of study.